2017
DOI: 10.1016/j.ijhm.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hospitality leaders’ relational transparency on followers’ trust and deviance behaviors: Mediating role of behavioral integrity

Abstract: This paper investigates the effect of leader's relational transparency on follower organizational deviance through followers' perception of leader's behavioral integrity and their trust in leader. Multi-level modeling results from a multisource survey-based field-study with 24 hospitality student project teams (N = 149) show that behavioral integrity mediates the relationship between leader's relational transparency and follower's trust in leader. Furthermore, multi-level path analysis suggests that leader's r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 75 publications
3
28
1
1
Order By: Relevance
“…As mentioned, there is very limited research on leader integrity in the foodservice industry. According to Gatling et al [12], the effect of leader transparency on followers cannot be underestimated in the hospitality industry, as it has considerable strategic effects, not only at the micro level, such as on followers' behaviors, but also at the macro level, such as on revenue and performance. Lack of leader integrity induces distrust among followers, making them hard to control at the organizational level.…”
Section: Leader Integrity In the Foodservice Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, there is very limited research on leader integrity in the foodservice industry. According to Gatling et al [12], the effect of leader transparency on followers cannot be underestimated in the hospitality industry, as it has considerable strategic effects, not only at the micro level, such as on followers' behaviors, but also at the macro level, such as on revenue and performance. Lack of leader integrity induces distrust among followers, making them hard to control at the organizational level.…”
Section: Leader Integrity In the Foodservice Industrymentioning
confidence: 99%
“…A recent meta-analysis also revealed that employees' assessments of the integrity of their leaders was clearly associated with the satisfaction, commitment, confidence, and the performance of the employees [11]. Despite the importance of integrity, however, little is currently known about how leader integrity is related to secondary responses-a connection that requires in-depth understanding, because employees in the foodservice industry in particular have significant social interactions with their leaders [12]. Studies of the relationship between leader integrity and an organization's members have, to date, mainly been conducted in terms of business administration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research shows that diminishing employees' faith in the organization can raise an individual's negative conduct (Mitchell and Ambrose 2007). Prior literature also shows a negative association between employees' trust and workplace deviance (Gatling et al 2017). Thus, the third hypothesis of this study is that:…”
Section: Employees' Trust and Workplace Deviancementioning
confidence: 71%
“…Based on Chan and McAllister (2014) and Dollard et al (2012) perspective, when employees develop low psychological safety, there may be implications for their attitudes, such as low identification toward leader and organization and high organizational deviance. Communication between leader and followers is a significant factor leading deviant behaviors (Gatling et al, 2017). The results show a positive communication will significantly improve employee involvement and identification with the leader (Guzley, 1992) because positive communication stimulates employees' self-expression, participation in group discussions, information and suggestion sharing, as well as learning (Smidts et al, 2001).…”
mentioning
confidence: 99%
“…In addition, open up communication with leader makes employees feel self-worth. This helps to avoid the deviant behaviors of employees (Gatling et al, 2017). As a result, mutual trust, support and a safe psychological atmosphere help employees never to be concerned about facing interpersonal risk effects, such as ridicule, censure, overlook and scolding (Dollard and Bakker, 2010;Edmondson, 1999Edmondson, , 2004.…”
mentioning
confidence: 99%